Análise da rede de atendimento à mulher em situação de violência - Carneiro, Cristianne Teixeira (2020)
Introduction: Epidemiological aspects indicate the significance of violence against women. To reduce damage to those who suffered this injury, the performance of the Service Network is critical to Women in Situations of Violence is important. Aim: To analyze the Assistance Network for Women in Situations of Violence, in a city in the Piauí state, Brazil, based on the perceptions of professionals in the areas of health, social assistance, public security and justice, in supporting and facing violence against women. Results: The analysis allowed the construction of three categories: A Network for Assistance to Women in Situation of Violence of a city in the interior of Piauí; Perceptions of professionals of the Service Network for Women in Situations of Violence regarding the services provided to the user; Weaknesses and Potentialities of the Service Network for Women in Situations of Violence. In the first category, it was perceived difficulty in performing matrixial cases of battered women, in primary care. In the Psychosocial Care Center, greater effectiveness of teamwork was observed. In the Service of Assistance to Victims of Sexual Violence, assistance to women who became pregnant during the crime was carried out by professionals who expressed conscientious objection to legal abortion. The flowcharts presented were not the only forms of organization of assistance to battered women, in the researched network. In the second category, the professionals’ perceptions of assistance to battered women were, predominantly, of violence veiled by women, the reasons being: psychological violence committed by the aggressor, hope that he will change his behavior, shame in society, loss of family support, emotional and economic vulnerability. There was a lack of professional qualification to identify cases of veiled violence and to deal with issues involved in this context. In the third category, the network’s weaknesses were: current political context; inadequate physical structure and equipment; insufficient number of professionals; absence of shelter houses; absence of routine communication between the health, social, legal and police sectors. The potential was: the ability of primary care teams to develop care technologies in the units and in the community; presence of women professionals and others with a humanized vision and who work hard; implementation of the Service of Assistance to Victims of Sexual Violence, offering free exams and drugs. Conclusion: It was demonstrated need for structural improvements; greater number of professionals and qualification through permanent education; drawing flowcharts of assistance to battered women; establishment of effective communication between the devices. Despite the identified weaknesses, professionals play an important role in assisting battered women. It was suggested reorganization of services in one place, with information sharing through data system, to avoid repetition of reports by women and facilitate access to the devices. These data design long way to go for managers and professionals, aiming to provide effective action in the research network.